Assessment of the application for renewal of authorisation of Formi™ LHS (potassium diformate) for sows. (27th February 2020) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of Formi™ LHS (potassium diformate) for sows. The Panel considers that the information provided by the applicant does not fulfil the minimum requirements to support that Formi™ LHS remains safe under the approved conditions for target species, consumers and users. The Panel concludes that the use of Formi™ LHS under the approved conditions remains safe for the environment. The present application for renewal of the authorisation does not include a proposal for amending or supplementing the conditions of the original authorisation that would have an impact on the efficacy of the additive.